THEORETICAL-CONCEPTUAL BASIS OF THE DEVELOPMENT MODEL OF UZBEKISTAN - Merzaev I. B.; Musaev A. J. (American Journals Publishing, 2023)
The article describes the development of society, the global socio-philosophical problems of mankind, the selection of a paradigm of development, which is one of the initial conditions of development after the independence of many countries.
Keywords: social, knowledge, current, methodology, problem, social development, model, general law.